HUBUNGAN PERSONAL HYGIENE TERHADAP KEJADIAN DIARE PADA BALITA DI WILAYAH KERJA PUSKESMAS AUR DURI KOTA JAMBI - Faradina Aghadiati; Liani Setyarsih; Mery Merlisia; Yolanda M. W Simatupang (Poltekkes Kemenkes Jambi, 2023)
Background: Diarrhea is a disease that is still an extraordinary problem. Factors that cause diarrhea include environmental sanitation, availability of clean water, personal hygiene, food sanitation, availability of toilet, and behavior of defecating. In Jambi Province, diarrhea ranks 7th out of the ten most common diseases that occur in Jambi Province Health Centers from 2016 to 2020. The results of the 2018 Basic Health Research, the prevalence of diarrhea in toddlers in Jambi Province is 9% and data from the Jambi City Health Office In 2021 shows that cases of diarrhea in Jambi City are 20%. Aur Duri Health Center in 2021 occupies the highest position in cases of diarrhea in toddlers, that is as many as 132 cases or 6% Method: This study used a quantitative method and a case-control approach. The sample in this study was 48 toddlers divided into 24 case samples and 24 control samples. The sampling technique used a purposive sampling technique and the data was analyzed univariately and bivariately using the Mann-Whitney test. Result: The results showed that there was no relationship between personal hygiene and the incidence of diarrhea, p-value of 0.391. Conclusion : The study concludes that there is no relationship between personal hygiene with the incidence of diarrhea in toddlers in the Work Area of the Aur Duri Community Health Center, Jambi City, in 2022